Phytochemical screening and acute oral toxicity assessment of Arenga pinnata leaf aqueous extract in Wistar rats - Ulfah Ulfah; Haniza Hanim Mohd Zain; Arfianti Arfianti; Salsabila Putri Balqis; Rizky Rajasa (Acta Biochimica Indonesiana, 2026)
Background: Arenga pinnata leaves have been traditionally used for medicinal purposes; however, their phytochemical composition and toxicity profile remain poorly characterized. Objective: This study aimed to identify bioactive compounds in A. pinnata leaf aqueous extract and evaluate its acute oral toxicity in Wistar rats. Methods: Qualitative phytochemical screening was performed using standard colorimetric and precipitation methods. Twenty-five male Wistar rats were randomly assigned to five groups (n=5): one control (distilled water) and four treatment groups receiving single oral doses of 200, 400, 800, and 1600 mg/kg body weight of aqueous extract. Animals were monitored for 14 days for mortality, behavioral changes, and clinical toxicity signs. Results: Phytochemical analysis confirmed the presence of alkaloids, flavonoids, tannins, and triterpenoids. No mortality, adverse clinical signs, or pathological organ changes were observed throughout the study period. All animals exhibited normal behavior and progressive weight gain. The median lethal dose (LD₅₀) exceeded 1600 mg/kg body weight, indicating low acute oral toxicity. Conclusion: A. pinnata leaf aqueous extract contains pharmacologically relevant bioactive compounds and demonstrates a favorable acute safety profile. These findings support traditional use while highlighting the need for sub-chronic and chronic toxicity studies.